Optimizing ibrutinib bioavailability: Formulation and assessment of hydroxypropyl-β-cyclodextrin-based nanosponge delivery systems - Sunitha Sampathi; Nitiraj Kulkarni; D.V.R.N. Bhikshapathi; Jagadish V. Tawade; Nainaru Tarakaramu; Rzgar Farooq Rashid; Aziz Kubaev (Current Research in Pharmacology and Drug Discovery)
Background: The current research aims to improve the oral bioavailability of ibrutinib (IBR), a class II drug with low solubility, through the formulation of nanosponges (NSPs) that incorporate IBR, utilizing Hydroxypropyl β-cyclodextrin (HPβCD) and 1,1′-carbonyldiimidazole (CDI) as cross-linking agent. Methods: IBR-loaded HPβCD-NSPs were formulated by optimizing the molar proportion of HPβCD to CDI, as well as stirring rate and duration using a design-based methodology. The synthesized nanoparticles (NSPs) were examined for size, potential, and entrapment of drug. Characterization was performed by X-ray diffraction analysis, Fourier Transform Infrared Spectroscopy (FT-IR), and Differential Scanning Calorimetry (DSC), to assess compatibility. Permeability studies were conducted, followed by in vitro and in vivo assessments. Results: The optimized IBR-loaded HPβCD NSPs demonstrated a mean particle size of 145.6 ± 6.8 nm, a PDI of 0.170 ± 0.036, and an EE of 71.04 ± 2.40%. Further validation through zeta sizing, microscopic and spectral analysis, release studies, and pharmacokinetic assessments confirmed the optimization. The HPβCD NSPs demonstrated 14.96 times higher AUC0-t (area under the curve) with a Cmax increase of 6.45 times compared to the free drug, indicating a substantial improvement in bioavailability. Conclusion: IBR-loaded HPβCD NSPs offer a promising strategy for improved drug release and bioavailability, which could significantly benefit melanoma treatment.